Supporting health education policies: translation, cross-cultural adaptation and validation of a health literacy instrument, in French - Clément, Céline; Lvovschi, Virginie-Eve; Verot, Elise; du Sartz de Vigneulles, Benjamin; Darlington-Bernard, Adeline; Bourgeois, Denis; Lamure, Michel; Vitiello, Flavia; Dussart, Claude; Carrouel, Florence (Frontiers in Public Health, 2023)
Background: Oral health is a fundamental human right and is inseparable and indivisible from overall health and well-being. Oral Health Literacy (OHL) has been proved to be fundamental to promoting oral health and reducing oral health inequalities. To our knowledge, no OHL instrument to evaluate OHL level is currently validated in French language despite the fact it is the fifth most widely spoken languages on the planet. The Oral health literacy Instrument (OHLI) appears to be the most interesting OHL instrument to adapt into French because it is already available in English, Spanish, Russian, Malaysian, and it contains both reading comprehension and numeracy sections. Its psychometric properties have been rated as adequate. Objective: The aim of this study was to translate and adapt cross-culturally the OHLI into French, to evaluate its psychometric properties and to compare its results to oral health knowledge. Method: This study followed and applied well-established processes of translation, cross-cultural adaptation and validation, based on the recommendations of the World Health Organization guidelines and on the Consensus-Based Standards for the Selection of Health Measurement Instruments (COSMIN) study design checklist for patient-reported outcomes. Two psychometric assessments were This is a provisional file, not the final typeset article planned, the comparison of OHLI-F scores according to education level and frequency of dental visits, and the test-retest reliability of the OHLI-F. Results: A total of 284 participants answered the OHLI-F. The OHLI-F scores were significantly different between participants with different levels of education and frequency of dental visits (p<0.001). Participants with an education level lower than the baccalaureate, and those who never visit the dentist or only in case of pain, had significantly lower OHLI-F scores. Internal consistency was excellent (Cronbach's alpha = 0.881 to 0.914). Test-retest reliability was very high (intraclass correlation = 0.985 to 0.996). Conclusion: The OHLI-F has demonstrated adequate psychometric properties and can therefore be used to measure oral health literacy in French-speaking populations.